2018
DOI: 10.1177/1533034617748429
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis Identified a Number of Dysregulated Long Noncoding RNA (lncRNA) in Human Pancreatic Ductal Adenocarcinoma

Abstract: Background:Long noncoding RNAs have been shown to play crucial roles in cancer biology, while the long noncoding RNA landscapes of pancreatic ductal adenocarcinoma have not been completely characterized. We aimed to determine whether long noncoding RNA could serve as early diagnostic biomarkers for pancreatic ductal adenocarcinoma.Method:We conducted a genome-wide microarray analysis on pancreatic ductal adenocarcinoma and their adjacent noncancerous tissues from 8 Chinese patients.Results:A total of 3352 sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…ADGRE5 , EDN1 , and STXBP6 are all involved in cell-cell adhesion [ [58] , [59] , [60] ], while EPN2 is involved in clathrin-mediated endocytosis and acts as a suppressor of VEGF-mediated angiogenesis [ 61 ]. The non-coding RNA genes TPRXL and SH3PXD2A-AS1 have both been linked to cancer as well [ 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…ADGRE5 , EDN1 , and STXBP6 are all involved in cell-cell adhesion [ [58] , [59] , [60] ], while EPN2 is involved in clathrin-mediated endocytosis and acts as a suppressor of VEGF-mediated angiogenesis [ 61 ]. The non-coding RNA genes TPRXL and SH3PXD2A-AS1 have both been linked to cancer as well [ 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are a class of non-protein-coding transcripts that are >200 nucleotides in length (5). Increasing evidence indicates that lncRNAs are crucial factors in tissue physiology and the pathological processes of various diseases, including cancer (6,7). A large number of dysregulated lncRNAs have been identified in cancer, suggesting their oncogenic or tumor-suppressive properties (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent translocations of PVT1 that arise through chromothripsis, such as PVT1-MYC and PVT1-NDRG1, often occur in malignant tumor [18]. Correlation analysis further revealed that the majority of lncRNA and mRNAs were negatively correlated, suggesting that lncRNAs were likely to serve as negative regulators of their targeting coding genes in PDAC tissues [19]. In addition, recent reports showed that PVT1 can be as a competing endogenous RNA to sponge miRNAs to governs cancer characters [6], [9], [20], [23].…”
Section: Discussionmentioning
confidence: 97%